The Effectiveness of Nutritional Interventions on Hypertension Control: A Meta-Analysis - Farras, Reyhan Muhammad (Newinera Publisher, 2024)
This study aims to evaluate the effectiveness of nutritional interventions in addressing hypertension, considering aspects such as food consumption, dietary patterns, and other nutritional interventions. Through meta-analysis, the research seeks to consolidate findings from various previous studies to provide a stronger conclusion regarding the effectiveness of nutritional interventions on hypertension and to establish a foundation for the development of more effective nutritional intervention programs for the prevention and control of hypertension. The research methodology employs a meta-analysis approach and literature research to evaluate relevant journal articles on the topics of